HUBUNGAN AKSESIBILITAS DAN FASILITAS TERHADAP KEPUSAN PENGHUNI DI RUSUNAWA KUDU, KECAMATAN GENUK, KOTA SEMARANG - Zethari Siregar, Friza; Puspo Priyadi, Budi; Hayu Dwimawanti, Ida (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
Accessibility refers to the ease of reaching a location or facility, while facilities encompass the infrastructure and amenities that enhance residents' comfort. This study aims to analyze the relationship between accessibility and facilities with resident satisfaction at Rusunawa Kudu, Genuk District, Semarang City. A quantitative approach was employed using a survey method based on the Guttman scale to measure residents’ responses regarding accessibility, facilities, and satisfaction. A total of 104 residents were selected as respondents through a stratified random sampling technique. Data were collected using questionnaires and analyzed through validity and reliability tests, Pearson correlation, multiple linear regression, and coefficient of determination to assess the contribution of each variable. The results show that accessibility and facilities, both partially and simultaneously, have a significant positive relationship with resident satisfaction. Accessibility factors, such as the ease of public transportation and proximity to public facilities, significantly contribute to residents’ comfort. Adequate facilities, including complete physical and infrastructure amenities, also significantly enhance resident satisfaction. The recommendations include improving accessibility through the provision of closer public transportation options and optimizing strategic locations. Furthermore, enhancing the quality and completeness of facilities is necessary to fully support residents' activities. This study is expected to contribute to Rusunawa managers and local governments in improving housing quality and resident satisfaction in the future.